Investigating the impairment-performance relationship during competition in elite blind and partially sighted football - Leivers, H. K.; Allen, P. M.; Timmis, M. A.; Runswick, O. R. (Frontiers in Sports and Active Living, 2025)
Introduction: Classification systems aim to minimise the impact of impairment on competition outcome. To measure the effectiveness of a classification system, the relationship between impairment and performance must be investigated. There are two forms of football for athletes with vision impairment (VI): blind football and partially sighted football. Athletes are allocated to either one based on VI severity. Research is yet to assess the impact of impairment on performance in competition; therefore, this study aimed to measure the impairment-performance relationship in male blind, partially sighted and women's blind football.